2017
DOI: 10.1105/tpc.17.00348
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Transcriptomes Stabilize Immunity to Pathogen Diversity: The Jasmonic Acid and Salicylic Acid Networks within the Arabidopsis/Botrytis Pathosystem

Abstract: To respond to pathogen attack, selection and associated evolution has led to the creation of plant immune system that are a highly effective and inducible defense system. Central to this system are the plant defense hormones jasmonic acid (JA) and salicylic acid (SA) and crosstalk between the two, which may play an important role in defense responses to specific pathogens or even genotypes. Here, we used the Arabidopsis thaliana-Botrytis cinerea pathosystem to test how the host's defense system functions again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
167
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(174 citation statements)
references
References 163 publications
(223 reference statements)
7
167
0
Order By: Relevance
“…It is worth noting that plant small‐molecule hormones, including jasmonic acid (JA) and salicylic acid (SA), play key roles in the plant response to V. dahliae infection (Glazebrook, ; Campos et al ., ; Zhang et al ., , ). However, we did not observe any significant differences in JA and SA levels (Figure S11) or changes in the expression of genes involved in these hormone signaling pathways between melatonin‐pre‐treated and control samples during V. dahliae infection (Figure S12).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that plant small‐molecule hormones, including jasmonic acid (JA) and salicylic acid (SA), play key roles in the plant response to V. dahliae infection (Glazebrook, ; Campos et al ., ; Zhang et al ., , ). However, we did not observe any significant differences in JA and SA levels (Figure S11) or changes in the expression of genes involved in these hormone signaling pathways between melatonin‐pre‐treated and control samples during V. dahliae infection (Figure S12).…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we had defined key transcript modules within both the host and pathogen transcriptomes that could be linked to virulence. Thus we proceeded to test if any of these trans-eQTL hotspots were associated with the previously defined transcript modules, by comparing gene lists for overlap between module membership and hotspot association (Zhang, Corwin et al 2017, Zhang, Corwin et al 2018 (Table 1). Nine of the 11 B. cinerea eQTL hotspots were enriched for transcripts present in one or more of four major B. cinerea co-expression networks on A. thaliana ( Figure 6).…”
Section: Eqtl Hotspot Modulesmentioning
confidence: 99%
“…To date in plants, co-transcriptome work where both the host's and pathogen's transcripts have been measured has been shown to work in the A. thaliana -B. cinerea system through single sample RNA-Seq (Zhang, Corwin et al 2017, Zhang, Corwin et al 2018. The genetic interactions between the extreme generalist pathogen, B. cinerea, and the model plant host, A. thaliana, are dominated by complex smalleffect loci that display a high degree of interaction between the host and pathogen (Denby, Kumar et al 2004, Rowe and Kliebenstein 2008, Zhang, Corwin et al 2017. Using this co-transcriptome approach to understand this system showed that it was possible to map key virulence networks in the pathogen and resistance responses within the host (Zhang, Corwin et al 2017, Zhang, Corwin et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations